Developing historical technical basis for radiological safety requirements of international transport safety regulations. (December 2013) - Bajwa, C.; Pope, R.; Baekelandt, L.; Zhao, Y.; Mennerdahl, D.
<x content-type="archive" xml:space="preserve">Abstract</x> The International Atomic Energy Agency (IAEA) is responsible for developing safety requirements for the transport of radioactive material. These requirements were first published in 1961 as 'Regulations for the Safe Transport of Radioactive Material', Safety Series No. 6 (the Regulations), and have been revised at regular intervals, in consultation with Member States, and with input from other relevant organisations, as appropriate. The current regular review and revision of the Regulations has been driven by problems, challenges and the demand for improvements, as well as the need to take into account experiences in transport, newly identified issues, new technologies, best practices, the demand for sustainable transport and harmonisation. After 50 years, 15 editions of the Regulations have been published. With the passage of time, the scientific and technical heritage of several decades of development in transport safety has begun to fade. The need to capture valuable knowledge, which needs to be preserved for future reference, has become clear. In general, every requirement in the regulations was developed on the basis of deliberations among international experts and an appropriate technical basis. The knowledge bases for these often exist in a decentralised manner in many Member States with mature nuclear programmes. Easier access to the existing technical bases for the Regulations could lead to a more comprehensive understanding of the Regulations. Knowledge capture and transfer can contribute to the development of and innovations in transport safety. This paper provides an overview of international level efforts that began in 2010 to develop a comprehensive and detailed technical basis document (TecBasDoc) to support the current and future revisions of the Regulations. The draft TecBasDoc has so far resulted from efforts by IAEA staff and a large number of international transport experts. It exceeds 150 pages in length using, to the greatest extent possible, historical documents dating as far back as the 1950s as reference material. The intent of this effort is to record, for those Member States new to transport and for future generations, the scientific and technical heritage of several decades of development that has occurred in transport safety and to capture valuable knowledge so it can be preserved for future reference. The latest effort has involved consultants to the IAEA adapting the draft to reflect guidance from the IAEA's Transport Safety Standards Committee (TRANSSC) and delving into the IAEA's archives and other sources of historical documents, searching out many long sought, older supporting documents. The draft is currently structured into 12 chapters, embodying multiple supporting appendixes. This paper elaborates on the first chapters of the document, which include General History, Fundamental Safety Principles, Safety Objectives and Principles for Transport, General Safety Requirements, Radiation Protection and Controls for Transport. Two companion papers at PATRAM 2013 address the status of the TecBasDoc in the topical areas of package testing and criticality control. In all cases, the chapters of the TecBasDoc address how early decisions were made citing well known historical experts and discussing how these initial decisions have been adapted to meet the emerging international safety guidelines.